Assessment of postoperative practices and discharge recommendations after radical prostatectomy - Melão, Bárbara Vieira Lima Aguiar; Assel, Melissa; Pere, Maria; Nalavenkata, Sunny; Touijer, Karim A.; Laudone, Vincent P.; Lin, Daniel W.; Rivas, Juan Gomez; Bjartell, Anders; Carlsson, Sigrid V. (Urologic Oncology: Seminars and Original Investigations, 2025)
Purpose: Consistent, accurate postoperative guidance is crucial for early recovery and patient satisfaction in urology, especially for radical prostatectomy (RP) patients. However, patients often receive inconsistent information, highlighting the need for standardized, evidence-based postoperative care guidelines. Materials and Methods: We conducted a comprehensive review and evaluation of current postoperative practices for RP. This involved (1) reviewing existing discharge information at Josie Robertson Surgery Center, Memorial Sloan Kettering Cancer Center to identify areas of improvement; (2) systematically evaluating inconsistencies in discharge instructions and their impact on patient care; (3) distributing an anonymous survey to urologists in the US and Europe via REDCap to gather insights into global postoperative care practices. The survey included questions on various aspects of postoperative care, such as catheter use, medication regimens, dietary restrictions, and physical activity guidelines. Results: We received 247 survey responses. Despite some consensus on certain postoperative practices and recommendations, significant variability existed, underscoring the lack of standardized guidelines. Notable differences were observed between US and European cohorts, particularly in postoperative length of stay and discharge practices. Only 1.4% of US responders discharged patients 3 or more days postsurgery compared to 46% in Europe. Variability was also noted in recommendations for erectile function medications and postoperative activity restrictions. Conclusion: This study underscores the significant variability in postoperative care recommendations for RP and the urgent need for standardized, evidence-based guidelines. Implementing such guidelines will enhance patient recovery, satisfaction, and overall outcomes, improving postoperative care across various surgical procedures.
Keywords: Evidence-based medicine; Postoperative care; Prostatectomy